The Influence of Profitability and Leverage to Tax Avoidance (Empirical Study of Consumer Goods Industry in Indonesia) - Sukmawati, Fitri (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine whether profitability and leverage affect tax avoidance on consumer goods industry sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The factors tested in this study are profitability and leverage as independent variables, while tax avoidance as the dependent variable. The research method used in this study is the verification method. The population in this study is companies in the consumer goods industry sector, amounting to 38 companies. The sampling technique used in this study was non probability sampling with a purposive sampling method, so the total sample was 30 companies. While the data analysis used in this study is panel data regression analysis at a significance level of 5%. The program used in analyzing data uses Eviews 9. The research results partially and simultaneously show that profitability and leverage affect tax avoidance. In addition, the results of the study also showed that the magnitude of the effect of profitability and leverage in giving contribution to tax avoidance was 38.8%.